Multimodal Rehabilitation After Anterior Cruciate Ligament Reconstruction: Evidence from Uzbekistan, Indonesia, and Iran - Karimov Dafron; Rahayu Sustiwi; Morteza Shamsi; Mobin Moradi (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the Study: This study aimed to compare multimodal rehabilitation approaches after anterior cruciate ligament reconstruction in Uzbekistan, Indonesia, and Iran. It examined the contribution of integrated rehabilitation interventions to improving knee function, restoring mobility, reducing postoperative complications, and supporting functional recovery across different healthcare and sports medicine contexts. Methodology: A comparative literature review was conducted using scientific publications and rehabilitation evidence from Uzbekistan, Indonesia, and Iran between 2020 and 2025. The analysis focused on integrated rehabilitation strategies, including therapeutic exercise, neuromuscular training, electrical stimulation, cryotherapy, massage therapy, and progressive strengthening programs for postoperative ligament reconstruction recovery. Main Findings: The findings indicated that multimodal rehabilitation consistently improved postoperative knee function, mobility, and functional performance across the three countries. Indonesian studies emphasized improvements in range of motion and edema reduction, Iranian research highlighted neuromuscular control and reinjury prevention, while Uzbek evidence demonstrated the role of therapeutic exercise and sports medicine integration. Despite differences in healthcare resources, integrated rehabilitation approaches showed comparable benefits for recovery after ligament reconstruction. Novelty/Originality of this Study: This study presents a cross-country synthesis of multimodal rehabilitation after anterior cruciate ligament reconstruction by integrating evidence from Uzbekistan, Indonesia, and Iran. It highlights similarities and contextual differences in rehabilitation strategies across diverse healthcare systems and sports medicine practices, offering a comparative evidence base that supports adaptation of multimodal rehabilitation protocols in developing country settings.